Appraising Customer Retention Strategies Employed By Malaysian Companies With Strategic Recommendations For Its Improvement - Abdulrahman M, Alaliani Reem (2009)
In this research, the objectives would be to make a research of the concept of customer retention and its importance in business success and enhanced profitability. This paper also aspires to research about the strategies that Malaysian companies use in order to retain a loyal customer base and to make determine the most appropriate methodologies that can be used by these companies in order to measure and manage customer value.